Pomer butyrylcholínesteráza/HDL-cholesterol a aterogénny index plazmy u pacientov so steatózou pečene - Turecký, Ladislav; Kupčová, Viera; Urfinová, Monika; Repiský, Marcel; Uhlíková, Eva (Vnitrni lekarstvi, 2021)
Cardiovascular diseases on an atherosclerotic basis are a serious health problem. Atherosclerosis is a multifactorial pathological process with complex pathogenesis. Its origin and development is conditioned by a set of several risk factors. Changes in the spectrum of lipoproteins are one of the well-known, serious risk factors for cardiovascular disease. The results of several authors showed, that the examination of the ratio of some lipoproteins can provide more accurate information about the cardiovascular risk in a given individual than the individual lipid parameters alone. Non-alcoholic fatty liver disease (NAFLD) is currently the most common form of chronic hepatopathy. The aim of our study was to examine lipoprotein ratios - atherogenic index of plasma (AIP) and butyrylcholinesterase/ HDL-cholesterol ratio - in patients with NAFLD and to evaluate their changes in relation to the severity of hepatic steatosis. The study group consisted of 64 patients with hepatic steatosis, 32 men and 32 women. Patients were examined for fatty liver index (FLI), with FLI values above 60.0 signaling the presence of steatosis. From the biochemical parameters, we examined the serum concentrations of total cholesterol, HDL- and LDL-cholesterol, triacylglycerols and butyrylcholinesterase activity in patients with fatty liver disease. As the results of our study showed, both basic lipid parameters - total cholesterol and triacylglycerols - were increased in patients with hepatic steatosis compared to the values in the control group (Chol: 3,59 ± 0,16 vs. 5,14 ± 0,14 mmol/l; TAG: 0,85 ± 0,06 vs. 1,86 ± 0,14 mmol/l). Both investigated lipoprotein ratios - AIP and the BChE / HDL-cholesterol ratio were also significantly increased in patients with liver steatosis (AIP: -0,191 ± 0,04 vs. 0,157 ± 0,04; BChE/HDL-C: 3171 ± 123 vs. 4602 ± 291). The value of the BChE/HDL-cholesterol ratio correlated well with the total cholesterol/HDL cholesterol ratio (correl.coeff. 0,802) as well as with the atherogenic index of plasma (correl.coeff. 0,702). The findings of elevated AIP and BChE/HDL-C ratios confirmed the hypothesis of an increased risk of cardiovascular disease in patients with fatty liver disease. The finding of a significant positive correlation between AIP and BChE/HDL-C on the one hand and fatty liver index (FLI) on the other hand suggests that cardiovascular risk increases with the severity of steatotic liver injury.
Keywords: Butyrylcholinesterase; butyrylcholinesterasa; Female; LDL-cholesterol; nealkoholová steatóza jater; Cholesterol, LDL; ženské pohlaví; triglyceridy; ratio BChE/HDL-cholesterol; Triglycerides; lidé; coronary artery disease; ratio total cholesterol/HDL-cholesterol.; Fatty liver; Atherosclerosis; atherogenic index of plasma; Male; Cholesterol, HDL; HDL-cholesterol; Non-alcoholic Fatty Liver Disease; ateroskleróza; butyrylcholinesterase; mužské pohlaví; cardiovascular risk; Humans